Clinicopathological study of premalignant and malignant lesions of cervix along with apoptotic index and Ki-67 expression - Atla, Bhagyalakshmi; Prasad, Uma; Samantra, Saraswathi; Botta, Venkata Satya Kartheek; Dasari, Naresh; Changala, Glen Christopher (International Journal of Research in Medical Sciences, 2020)
Background: Cervical cancer is known to have a good response to radiotherapy. The response and prognosis are dependent on the level of apoptosis. Pap smear and histopathology are cost-effective methods in diagnosing premalignant and malignant lesions of cervix but not accurate in classifying and estimating the progression of the disease, especially in premalignant lesions. Therefore this study was undertaken to know the role of Ki-67 expression and apoptotic index in classifying accurately the premalignant lesions for better management. Methods: The study included 540 cases diagnosed histologically as cervical intraepithelial neoplasia or carcinoma. The apoptotic index is calculated for all the 540 cases using light microscopy on Haematoxylin and Eosin stained sections. Ki-67 immunohistochemical staining was done for 100 cervical biopsies. Ki-67 expression was graded and the Ki-67 labelling index was calculated. Statistical evaluation was done using the unpaired t-test. Results: The Apoptotic index increased with increasing grade of dysplasia. There is a significant difference in the mean apoptotic index between premalignant and malignant lesions of the cervix. The ki-67 index increased with increasing grade of dysplasia. There is a significant difference in the mean Ki-67 index between premalignant and malignant lesions of the cervix. Conclusions: Apoptotic index and proliferative indices have been found useful in distinguishing between premalignant and malignant lesions of the cervix and gives an idea about the proliferative activity of the tumour for better management of the patient and to determine prognosis.